Business resilience system (BRS) : driven through boolean, fuzzy logics and cloud computation : real and near real time analysis and decision making system /: driven through boolean, fuzzy logics and cloud computation : real and near real time analysis and decision making system. (2017) - Zohuri, Bahman; Moghaddam, Masoud
No abstract available